The Role of Lymphadenectomy Versus Sentinel Lymph Node Biopsy in Early-stage Endometrial Cancer: A Review of the Literature. (October 2016) - Tschernichovsky, Roi; Diver, Elisabeth J.; Schorge, John O.; Goodman, Annekathryn
Abstract : Objective: The objective of this study is to review existing data regarding the feasibility, diagnostic performance, and oncologic outcomes of sentinel lymph node biopsy (SLNB) versus lymphadenectomy (LND) in endometrial cancer. Materials and Methods: A PubMed search identified studies on different staging strategies in endometrial cancer, including routine LND, predictive models of selective nodal dissection, and SLNB. Results: There is ongoing controversy over the risk-benefit ratio of LND in assessing nodal involvement in presumed early-stage endometrial cancer. Current experience with sentinel node biopsy suggests high detection rates and low false-negative rates across most series, as well as the increased detection of occult metastatic disease overlooked by conventional pathology. Although data on the long-term oncologic outcomes of sentinel node biopsy in this setting are limited, short-term follow-up shows no immediate impairment of disease-free survival or overall survival rates when compared with LND. Conclusions: SLNB holds promise as a less-morbid and more accurate alternative to LND for determining nodal spread in early-stage endometrial cancer. Further studies are necessary to understand how lymph node status will guide postoperative management and impact survival of women with nodal metastases.